2017
DOI: 10.1017/s0007114517002495
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, nutritional status and mental wellbeing of homeless adults in Reading, UK

Abstract: Malnutrition has been reported in the homeless, yet the specific nutritional issues faced by each homeless community are unclear. This is in part due to nutrient intake often being compared with dietary reference values as opposed to a comparative housed population. In addition, the complex interplay between nutrient intake, reward mediated behaviour and mental illness is frequently overlooked. This study aimed to compare the dietary intake, nutritional status and mental wellbeing of homeless and housed adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Of 2122 identified studies, 37 were identified as potentially-relevant (Table 1). These studies reported on 73 health screening or health assessment tools, across 11 domains: oral health [22–32]; health related quality of life, and health status [9, 3348]; nutrition [49–56]; psychological and cognitive function [9, 22, 34, 35, 41, 42, 44, 56–59]; substance use [28, 3336, 51, 57]; injury [29, 30, 36, 58]; chronic conditions [33, 44, 45, 60, 57]; demography and anthropometry [3440, 44, 49, 5155, 60]; functional decline and frailty [9, 37, 38, 54]; hearing and vision [9, 36, 61]; and pelvic floor health [9].…”
Section: Resultsmentioning
confidence: 99%
“…Of 2122 identified studies, 37 were identified as potentially-relevant (Table 1). These studies reported on 73 health screening or health assessment tools, across 11 domains: oral health [22–32]; health related quality of life, and health status [9, 3348]; nutrition [49–56]; psychological and cognitive function [9, 22, 34, 35, 41, 42, 44, 56–59]; substance use [28, 3336, 51, 57]; injury [29, 30, 36, 58]; chronic conditions [33, 44, 45, 60, 57]; demography and anthropometry [3440, 44, 49, 5155, 60]; functional decline and frailty [9, 37, 38, 54]; hearing and vision [9, 36, 61]; and pelvic floor health [9].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, healthier and more expensive items, such as meat, fish, vegetables, and fruits have been less often consumed by homeless ( 33 , 36 , 38 , 39 ), which may be a contributing factor to the low T. gondii seroprevalence found in this study. Hence, it is reasonable to speculate that the beneficial shelters, hostels, and meal services may have offered protection to the homeless population ( 36 , 40 ) but not as nutritional good food habits when compared to the general population.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, healthier and more expensive items such as meat, sh, vegetables, and fruits have been less often consumed by homeless [33,36,38,39], which may bea contributing factor to the low T. gondii seroprevalence found in this study. Hence, it is reasonable to speculate that the bene cial shelters, hostels, and meal services may have offered protection to the homeless population [36,40] but not as nutritional good food habits when compared to the general population.…”
Section: Discussionmentioning
confidence: 93%